Severe Acute Respiratory Syndrome Coronavirus 2: From Gene Structure to Pathogenic Mechanisms and Potential Therapy - Wu, Jun; Yuan, Xiaohui; Wang, Bing; Gu, Rui; Li, Wei; Xiang, Xuemei; Tang, Lijun; Sun, Hongyu (Frontiers in Microbiology, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a newly emerging respiratory virus with high morbidity, which was named coronavirus disease 2019 (COVID-19) by World Health Organization (WHO). COVID-19 has triggered a series of threats to global public health. Even worse, new cases of COVID-19 infection are still increasing rapidly. Therefore, it is imperative that various effective vaccines and drugs should be developed to prevent and treat COVID-19 and reduce the serious impact on human beings. For this purpose, detailed information about the pathogenesis of COVID-19 at the cellular and molecular levels is urgently needed. In this review, we summarized the current understanding on gene structure, protein function, and pathogenic mechanisms of SARS-CoV-2. Based on the above, we refined the correlations among gene structure, protein function and pathogenic mechanisms of SARS-CoV-2. Importantly, we further discussed potential therapeutic targets, aiming to accelerate the advanced design and development of vaccines and therapeutic drugs against COVID-19.